Rancang Bangun Aplikasi Monitoring Karyawan Dan Perkembangan Proyek Berbasis Android Pada PT. Arhanindo Pratama - Vadri, Yasminne R.A.S; Marpaung, Noveri Lysbetti (CSRID (Computer Science Research and Its Development Journal), 2024)
Employees are human resources who play an important role in determining the performance achievements of a company. Employees with good performance are employees who have several characteristics such as being disciplined, responsible, and able to work together. To find out employee performance, monitoring is necessary, such as monitoring employee attendance in the office. Unfortunately, PT. Arhanindo Pratama does not currently have a system for daily attendance, making it difficult to monitor employee attendance. This can cause employees to deliberately come in late or even not show up. Employee absences lead to a lack of collaboration and discussion, hindering project progress. Monitoring project progress is also difficult due to lack of information about the project from absent employees. Based on these problems, research was carried out by creating an Android-based employee monitoring and project development application. Employees will be able to check in and out, view history, and see a list of ongoing projects. The application will be created using the Kotlin programming language and tested in four aspects consisting of functionality, portability, compatibility and usability. The results of functionality testing are that all functionality was successfully tested with a feasibility percentage of 100%. In portability testing, the results showed that the application can run on various devices and different versions of Android. Compatibility testing shows that the application can run in split-screen mode. Then, usability testing was carried out using UEQ which showed excellent results, namely attractiveness with a value of 2.37, perspicuity with a value of 2.27, efficiency with a value of 2.20, dependability with a value of 2.15, stimulation with a value of 2.22, and novelty with a value of 2.15.